Radikalisme Agama-Agama Abad 21 - Afif Muhammad (Al-Jami'ah: Journal of Islamic Studies, 2003)
When the world will come to the millennium era, there are some hopes that the world will be more peaceful. However, the phenomena emerged prior to the millennium era is on the other way around. One of the phenomena is the rise of religious radicalism which worsened the political system of the world. Religious radicalism is not only happened in Muslim world, but it also happened to other religious in the west. In the East, Islamic radicalism are occurred due to some factor. First the development of ideological understanding in Muslim society is happened simultaneously with their struggle too free their countries from Western colonialism. Second, normative and textual understanding of Islam developed which disregard the truths from other parts. The third is uprising of the resistant attitude of Muslim in several parts of the world such as Pakistan and Afghanistan, along with the unjust way of behaving of western countries to some Muslim. Meanwhile, religious radicalism in the West was, due, in part, to capitalism and colonialism. In Indonesia, religious radicalism emerged along with the incident of 11 September 2000. Religious conflict and Bali Bombing are several of the religious should try their best to overcome this problem by conducting religious and cultural dialog among them, along with the fair and just attitude among them as well.